Implementación de un cangrejal – marisquería en el Cantón Urdaneta - KATE - Chico Mecias, Katherine Dayana (2019)
consumption of red crab in Ecuador is high and the demand for this crustacean is increasing every year, because it is used in the preparation of a variety of dishes à la carte. This growing trend generated the opportunity to develop the present proposal for the future implementation of a Cangrejal - Marisquería in the Urdaneta Canton of the Province of Los Ríos. In the mentioned Canton there is only one informal place where said crustacean is offered, so the proposed business model generates a very significant value proposal that includes: pleasant and welcoming atmosphere, personalization of the service and a standardized price below the competition , making this an attraction for customers. In the scalability of the business it is proposed to offer other seafood such as shrimp, shell and fish, in a la carte dishes, giving greater emphasis in the two periods of the crab ban.